The impact of Covid-19 on recovery after sexual violence and abuse: Voices of help-seeking survivors and those individuals working within specialist support services in England - Sleath, Emma (International review of victimology, 2025)
We examined the impact of Covid-19 on service delivery within specialist sexual violence services and the healing journeys of survivors of sexual violence and abuse through the experiences of 22 professionals and 221 service users in England. The pandemic posed challenges across all sectors and economies across the globe, but practices and innovations that emerged at that time could enhance future services and user experiences. Thematic analysis was used to identify key themes within the data. Overall, the negative impacts of Covid-19 outweighed the positive changes: survivors reported increased feelings of depression, anxiety, and worry, exacerbated by isolation and lost connections with friends and family, and access to strategies for managing their mental health. Difficulties/delays in accessing support, service provision, and disruptions to rapport, trust, and safety were widespread in participants’ reports. Conversely, for some, requirements to remain at home provided safety from the world, and space for healing, and even prompted survivors of non-recent abuse to seek help. Remote service delivery was beneficial where clients could be ‘at a distance’ in discussing sensitive issues. Together with insights from professionals about their own isolation, blurred boundaries, and concerns regarding client confidentiality and engagement, this research highlights an agile sector responding to an unprecedented situation. Moving forward, survivors’ preferences for flexible/remote support must be integrated into everyday delivery.